THE LEVEL OF KNOWLEDGE WITH CITIZENS’ BEHAVIOR IN IMPLEMENTING HEALTH PROTOCOL IN THE NEW NORMAL TIME OF THE COVID-19 PANDEMIC IN ARA CONDONG VILLAGE, KEC. STABAT KAB. LANGKAT, YEAR 2021 - Juliati Juliati; Aisyah Aisyah (Institute of Computer Science (IOCS), 2021)
Knowledge is the result of